White fang - London, Jack; Madsen, James (Usborne Publishing London, 2015)
Jack London's classic novel - the complete and unabridged text, fully illustrated by Jim Madsen. The story of one wolfdog's epic journey from cub to sled dog to fighting dog. Living in harsh surroundings with brutal owners, every day is a battle for survival for White Fang. 8 yrs+